The association of attention deficit hyperactivity disorder (ADHD) levels of severity and substance use in youths and young adults - Magnea Björg Friðjónsdóttir 1999- (2022)
Attention Deficit Hyperactivity Disorder (ADHD) has been linked with a greater risk of substance use initiation among youths, more frequent lifetime prevalence, more severe substance use, and more rapid development of dependence. Few studies have studied the relationship while considering ADHD severity levels, which was added in the latest edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). This study aimed to acquire a greater understanding of those relations by assessing substance use for the three severity levels of ADHD symptoms; mild, moderate, and severe, and compare them to a baseline group of individuals with insufficient ADHD symptoms. Data from the Youth in Iceland 2013 survey was used for the statistical analysis. The sample consisted of 2222 participants, randomly selected from 11,116 students in 31 high schools in Iceland that took part in the study (age range 15 to 23 years old, M = 17.5, SD = 1.4). Analysis of covariance was used to study differences in substance use by ADHD severity levels while adjusting for known covariates. The relations were also tested without adjusting for covariates, and to measure early onset of substance use by ADHD severity levels. The results indicated that substance use differs significantly between ADHD levels of severity, where youths with higher severity levels engage in more substance use behavior with a gradually earlier initiation. Keywords: Attention Deficit Hyperactivity Disorder, Substance Use, Young Adults, ADHD levels of severity Athyglisbrests- og ofvirkniröskun (ADHD) hefur verið tengd við aukna áhættu á snemmbúnu upphafi vímuefnaneyslu meðal ungmenna, alvarlegri vímuefnaneyslu og hraðari þróun ánetjunnar, sem og hærri tíðni áframhaldandi neyslu til framtíðar. Fáar rannsóknir hafa rannsakað tengslin með tillit til áhrifa alvarleikasigs ADHD, sem var bætt við í nýjustu útgáfu Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Þessi rannsókn miðar að því að öðlast aukin skilning á sambandinu með því að meta ...